GRAVES’ DISEASE PRESENTING WITH SUPERIOR MESENTERIC ARTERY SYNDROME - Diah, Mohd Idris; Hui, Wong Kwong; Ching, Tee Hwee; Hui, Ho Jin (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Superior Mesenteric Artery (SMA) syndrome is a rare manifestation of small bowel obstruction caused by compression of the third portion of the duodenum between the SMA and aorta. It is associated with extreme weight loss due to malnutrition/malabsorption, hypermetabolism or cachexia-causing conditions such as malignancy. We report a case of SMA syndrome due to acute weight loss secondary to undiagnosed Graves’ disease. CASE A 63-year-old female with a medical history of schizophrenia in remission, presented to the emergency department with a two-week history of persistent postprandial vomiting and upper abdominal pain. She had a history of unintentional weight loss of approximately 11 kg over 3 months. On examination, she appeared cachectic. She had a blood pressure of 137/72 mmHg and a heart rate of 120 bpm. Thyroid function tests showed severe hyperthyroidism with TSH <0.01 m IU/L and FT4 100 pmol/L. She had elevated TSH receptor antibodies of 32.7 IU/L. Her abdominal CT revealed a grossly distended stomach filled with oral contrast and significant narrowing at the D4 level of the duodenum. She was diagnosed with SMA syndrome secondary to Graves’ disease. Hence, she was treated with nasogastric intubation for gastric decompression, total parenteral nutrition, antiemetic, PTU per rectal, Lugol’s iodine and intravenous propranolol to control her thyrotoxicosis. Despite conservative treatment and normalisation of FT4 level, the patient had persistent symptoms hence she underwent exploratory laparotomy and duodenal kocherisation. Postoperatively, her symptoms improved. She was able to resume a normal diet and continued to gain weight appropriately. CONCLUSION This case highlights the importance of considering SMA syndrome in patients with Graves’ disease presenting with gastrointestinal symptoms and rapid weight loss. Prompt treatment of thyrotoxicosis alongside nutritional optimization and duodenal obstruction relief by conservative or surgical management is equally crucial.